Isolated fatty infiltration of the gastrocnemius medial head, a cadaveric case study - Karyne N. Rabey; Lalith Satkunam; Christine A. Webber; Jennifer C. Hocking (Elsevier, 2021)
Gastrocnemius is a superficial calf muscle with two muscular heads that contribute fibres to the Achilles tendon. While gastrocnemius functions during movement of the knee and ankle joints, the muscle is of particular clinical interest as a target for treatments to alleviate lower limb spasticity and pain. Here, we describe abnormal calf musculature discovered incidentally during cadaveric dissection in an anatomy teaching laboratory. In particular, the medial head of the gastrocnemius in the left leg exhibited almost complete replacement by adipose tissue, while the lateral head and soleus muscles were unaffected. On the right side, the medial head again showed fatty infiltration, but only in the distal part of an otherwise substantial muscle belly. While the nerve to the left medial head was intact, a cyst was discovered in the sacral vertebral column. The full, but isolated replacement of a muscle belly by fat is a highly unusual finding. Potentially, muscle degeneration followed by fatty infiltration was secondary to compression of the S1, S2 nerve roots and denervation of the muscle, but other possible causes are reviewed in the discussion.